Bibliometric Analysis of IoT in Smart Governance - Loso Judijanto (Westscience Press, 2026)
This study explores the intersection of the Internet of Things (IoT) and smart governance through a comprehensive bibliometric analysis. Using data from the Scopus database, the analysis identifies key research trends, influential publications, and emerging technologies in this domain. The findings reveal a growing focus on IoT’s role in enhancing urban governance, with an emphasis on sustainability, smart city development, and the integration of advanced technologies such as blockchain, machine learning, and predictive analytics. This research highlights the evolution of IoT in public administration and offers a structured overview of the academic landscape, uncovering the most influential topics and providing insights into future research directions.